High performance computing for computational science -- VECPAR 2016 : 12th International Conference, Porto, Portugal, June 28-30, 2016, Revised Selected Papers /: 12th International Conference, Porto, Portugal, June 28-30, 2016, Revised Selected Papers. (2017) - Unknown
No abstract available